High-risk family colorectal cancer screening service in Ireland: Critical review of clinical outcomes. (October 2017) - Walshe, Margaret; Moran, Robert; Boyle, Marie; Cretu, Ion; Galvin, Zita; Swan, Victoria; Trikovic, Jason; Farrell, Michael P.; Foy, Sinéad; O'Brien, Loretta; Leyden, Jan; Mulligan, Niall; et al.
Highlights: Our high-risk screening clinic relies on patients to report family cancer history. Most patients seeking familial CRC screening are too young for population screening. Male gender and increasing age are associated with higher neoplastic yield. Adenomas at index colonoscopy are predictive of adenomas at subsequent colonoscopy. Our results support less intensive screening in patients <50yrs, and where index colonoscopy is normal. Abstract: Background: We present the 15-year experience of a family colorectal cancer screening service in Ireland with emphasis on real life experience and outcomes. Methods: Questionnaires were used to assess family cancer history and assign patients to risk categories; 'Moderate Risk', HNPCC, (suspected) genetic syndrome (non-HNPCC), 'Low Risk'. Screening was by full colonoscopy. We report neoplastic yield, examining effect of risk category, age, gender, and index colonoscopy findings. Results: Between 1998 and 2013, 2242 individuals were referred; 57.3% female, 42.7% male, median age 46 years (range9-85yrs). Median follow up time was 7.9yrs (range 0.5-15.3yrs). Follow up data after exclusion (non-compliance, known CRC) was available in 1496 (66.7%): 'Moderate risk' 785 (52.5%), HNPCC 256 (17.1%), (suspected) genetic syndrome (non-HNPCC) 85 (5.7%), 'Low Risk' 370 (24.7%). Screening was performed in 1025(68.5%) patients; colonoscopy data available for 993 (96.9%); total 1914 colonoscopies. At index colonoscopy, 178 (18.0%) patients had adenomas; 56 (5.5%) advanced adenoma. During the entire study period, 240 (24.2%) had an adenoma; 69 (7.0%) advanced adenoma. Cancers were diagnosed on screening in 2 patients. Older age and male gender were associated with higher adenoma detection rate; p < 0.001, p = 0.01, respectively. Risk category did not affect adenoma yield. Adenoma and advanced adenoma detection at index colonoscopy were associated with detection of same at follow up screening; p < 0.001. Conclusion: Male gender and age (>50) were the core identifiable risk factors for neoplasia at screening colonoscopy in this family screening setting. Our results would support less intensive surveillance in younger patients (<50), particularly where index colonoscopy is normal.